Structural validity and reliability of the healthcare professionals' economic reasoning questionnaire - Vuković Mira H.; Jakovljević Mihajlo B. (Srpsko lekarsko drustvo, 2015)
Introduction: The structure of healthcare professionals' economic reasoning (HPER) is still unknown. The aim: The structural validity and the reliability of the HPER questionnaire were evaluated. Methods: The psychometric study about evaluation of the HPER factors was conducted. The healthcare professionals (physicians, dentists, pharmacists) that are employed in healthcare state sector of Republic of Serbia were interviewed. The HPER Questionnaire contained 29 preliminary items. Its structure was evaluated by Principal Component Analysis for categorial and ordinal data. Results: The 9 items that defined seven HPER factors were extracted: (1) the negligence of the cost of quality by the administration and financier; (2) the consideration of the market price and healthcare benefit; (3) market orientation considering patient's requests; (4) the recognition of inadequate resource alocations by non-medical administrative authority; (5) the attitude about redirecting the profit from state to private healthcare sector; (6) the recognition of the unjustified spending by the healthcare professionals and (7) the relationship physician/patient. Conclusion: The HPER-9 Questionnaire has high structural validity and reliability in the HPER measurement.